2019
DOI: 10.1038/s41598-019-44418-6
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Interlocking Dissolving Microneedles for Accurate and Efficient Transdermal Delivery of Biomolecules

Abstract: The interest in safe and efficient transdermal drug delivery systems has been increasing in recent decades. In light of that, polymeric dissolving microneedles (DMNs) were developed as an ideal platform capable of delivering micro- and macro-biomolecules across the skin in a minimally invasive manner. A vast majority of studies, however, suggest that the shape of DMNs, as well as the elastic properties of skin, affects the delivery efficiency of materials encapsulated within DMNs. Likewise, in dynamic tissues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Drug-encapsulated DMNs are generally fabricated in arrays onto sticky patches and applied onto the skin for minutes to hours, depending on the type and viscosity of their backbone matrix materials [22,23,24,25]. Fabricating DMNs over patches, however, was shown to affect delivery accuracy and reduce the efficiency of the encapsulated drugs, due to the incomplete penetration of DMNs into the skin [26,27]. The vast majority of studies showed that because of the physico-chemical properties of the skin, DMNs are not completely inserted into it, resulting in a random and inconsistent release of encapsulated compounds with each application [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-encapsulated DMNs are generally fabricated in arrays onto sticky patches and applied onto the skin for minutes to hours, depending on the type and viscosity of their backbone matrix materials [22,23,24,25]. Fabricating DMNs over patches, however, was shown to affect delivery accuracy and reduce the efficiency of the encapsulated drugs, due to the incomplete penetration of DMNs into the skin [26,27]. The vast majority of studies showed that because of the physico-chemical properties of the skin, DMNs are not completely inserted into it, resulting in a random and inconsistent release of encapsulated compounds with each application [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugation of the secondary droplet created a double-layered PBM with a narrow neck, a wide mid-portion, and a sharp tip (Figure 1a). PBMs, because of their morphology, are capable of achieving a precise implantation of micro-pigments without utilizing an applicator [28]. Thus, individuals can use finger force to apply PBMs to the targeted scalp region and achieve a highly accurate implantation (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…PBMs comprise a micro-dimensioned polymeric transdermal system designed to implant the encapsulated micro-pigments in a minimally invasive manner [25,26,27]. A recently developed fabrication technique that produces a “tissue interlocking dissolving microneedle”, capable of the accurate delivery of encapsulated materials, is employed to achieve a precise implantation of micro-pigments below the epidermis [28]. PBMs comprise an unpigmented base layer, acting as a shaft to implant micro-pigments beneath the epidermis, and a micro-pigment encapsulating top layer.…”
Section: Introductionmentioning
confidence: 99%
“…A further development of DAB is the centrifugal lithography (CL),8b in which the droplets are shaped and solidified into MN by centrifugal force under vacuum condition. A wide range of needle geometry (i.e., sharp needle, swollen body, narrow base) can be made through the CL method . For example, a wine glass‐shaped primary layer was constructed with a primary wine glass‐shaped layer and a sharp tip secondary layer.…”
Section: Polymeric Microneedlesmentioning
confidence: 99%